Optimization analysis of straight-bladed vertical axis wind turbines in turbulent environments by wind tunnel testing. (1st April 2022) - Peng, H.Y.; Zhong, B.W.; Hu, G.; Liu, H.J.
Highlights: VAWT efficiency greatly improves in turbulence, but almost plateaus as Iu further increases. Solidity and pitch can yield order-of-magnitude improvements in turbine performance. Extent of efficiency improvement by turbulence decreases when factors approach optimum. Toe-out pitch ranging from −9.5° to −6.5° is recommended for H-rotor VAWTs. Extent of impact of factors on the performance of VAWTs ranks as: β  >  σ  >  η  >  Iu . Abstract: Although freestream turbulence is believed to improve the efficiency of vertical axis wind turbines (VAWTs), few studies have systematically assessed VAWT performance in turbulent environments. In this study, steel and aluminum grids were used to simulate the turbulence field. Three turbulence levels of Iu  = 5.1%, 10.9% and 14.6% were generated, together with one low turbulence level of 0.9%. First, the parametric effects of solidity ratio σ, pitch angle β, and aspect ratio η were examined in 48 cases in various flow regimes. Then, the Taguchi method with an L16 (4 4 ) orthogonal table was implemented to comprehensively and effectively investigate the parametric effects and their extent of impact on VAWT turbine performance. This reduced the number of cases from 256 to 16. Unlike smooth flow, turbulence enhanced the efficiency of the VAWTs, with improvements ranging from 7.9% to 38.0%. The factors influenced efficiency in the following order: β  >  σ  >  η  >  Iu . The VAWT performance peaked at β  = −6.5°, and revealed that a toe-out pitch ranging from −9.5° to −6.5° is required for maximal performance. The improvements in VAWT efficiency caused by turbulence decreased as a factor approached its optimal value.